Seasonal atmospheric deposition variations of polychlorinated biphenyls (PCBs) and comparison of some deposition sampling techniques - Birgul, Askin; Tasdemir, Yucel (SPRINGER HEIDELBERG, 2011)
Ambient air and bulk deposition samples were collected between June 2008 and June 2009. Eighty-three polychlorinated biphenyl (PCB) congeners were targeted in the samples. The average gas and particle PCB concentrations were found as 393 +/- 278 and 70 +/- 102 pg/m(3), respectively, and 85% of the atmospheric PCBs were in the gas phase. Bulk deposition samples were collected by using a sampler made of stainless steel. The average PCB bulk deposition flux value was determined as 6,020 +/- 4,350 pg/m(2) day. The seasonal bulk deposition fluxes were not statistically different from each other, but the summer flux had higher values. Flux values differed depending on the precipitation levels. The average flux value in the rainy periods was 7,480 +/- 4,080 pg/m(2) day while the average flux value in dry periods was 5,550 +/- 4,420 pg/m(2) day. The obtained deposition values were lower than the reported values given for the urban and industrialized areas, yet close to the ones for the rural sites. The reported deposition values were also influenced by the type of the instruments used. The average dry deposition and total deposition velocity values calculated based on deposition and concentration values were found as 0.23 +/- 0.21 and 0.13 +/- 0.13 cm/s, respectively.
Keywords: Bulk deposition; Deposition flux; Deposition velocity; PCB congeners; POLYCYCLIC AROMATIC-HYDROCARBONS; HYDROPHOBIC ORGANIC CONTAMINANTS; WET DEPOSITION; DRY DEPOSITION; ORGANOCHLORINE PESTICIDES; SUBMICRON PARTICLES; INDUSTRIAL SITE; LAKE-MICHIGAN; GAS-EXCHANGE; Environmental Sciences & Ecology